Mechanisms and long-term evolution of river valley contractions after impoundment in the upstream reservoir area of Baihetan - Mayong Jiang; Zhongjie Yu; Bowen Li; Zuhao Lyu; Guan Rong (European Journal of Environmental and Civil Engineering, 2026)

Experimental study of seepage and water-rock heat transfer in granite fracture under chemical action - Ruotao Liu; Guan Rong; Bowen Li; Zhongjie Yu; Huqi Zhang; Qinyan Qiu (European Journal of Environmental and Civil Engineering, 2026)

A nonlinear constitutive model for fine sandstone considering freeze–thaw induced compaction and damage evolution - Qi Wu; Ruichen Luo; Bowen Li; Qinyan Qiu; Maiyong Jiang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Burkholderia cepacia NB-13: Biocontrol efficacy and medium-driven metabolic regulation - Zhou Yin; Xiaoqin Li; He Guan; Dindi Tu; Xingyi Luo; Wancheng Hu; Fanqian Zhou; Menglong Li; Shulin Liu; Hui Li; Rong Song; Kailin Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

Separation of V/Cr from the leachate of vanadium slag by solvent extraction to prepare vanadium electrolyte - Rong Jiang; Limei Chen; Qiuxiang Liu; Mingyu Wang; Guiqing Zhang; Qinggang Li; Wenjuan Guan; Shengxi Wu; XinSheng Wu (Hydrometallurgy, 2026)

Seed dispersal drives competition between pair-growing trees: implications for forest community dynamics - Xifu Yang; Haifeng Gu; Guangshun Jiang; Ke Rong; Hongjun Li; Qinghua Zhao; Yanhui Guan; Feifei Yang; Wentao Zhang; Tongzuo Zhang; Zhibin Zhang (Plant Ecology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

Association between plasma trace metals and non-alcoholic fatty liver disease among rural women in Southern China - Qiumei Liu; Xiaolin Li; Yufu Lu; Kaisheng Teng; Xiaoting Mo; Linhai Zhao; Songju Wu; Jiahui Rong; Qinyi Guan; Lei Luo; Tiantian Zhang; Yujian Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Integrated Analysis of Midgut Transcriptome and Microbiome Reveals That Manganese‐Induced Dysbiosis Drives Metabolic Disruption and Developmental Toxicity in Bombyx mori - Lei Xin; Yazhen Chen; Delong Guan; Lida Huang; Yiwei Lv; Wantao Rong; Xiaodong Li (Environmental Microbiology, 2026)
Manganese (Mn) contamination poses a significant environmental threat, yet the mechanisms underlying its toxicity remain poorly characterised. Here, we used an integrative multi‐omics approach to elucidate how dietary Mn disrupts the gut‐microbiome axis in the silkworm, Bombyx mori . High‐dose Mn exposure triggered severe, dose‐dependent growth retardation, reducing larval weight by 55.1%. This was concurrent with profound gut microbiome dysbiosis, evidenced by reduced bacterial diversity, community homogenisation and a sharp decline in beneficial genera such as Delftia , alongside the complete elimination of key commensals like Bifidobacterium . Host midgut transcriptomics revealed 1255 differentially expressed genes, with significant upregulation of detoxification and stress pathways and marked suppression of genes involved in nutrient metabolism. Critically, integrative analysis demonstrated a strong correlation between microbiome disruption and host metabolic gene expression, suggesting that Mn toxicity operates by disrupting the gut microbiome‐host metabolic axis. Our findings provide crucial mechanistic insights into heavy metal ecotoxicology and highlight the vulnerability of beneficial insect‐microbe symbioses to environmental contamination, with important implications for sustainable agriculture in metal‐polluted regions.

Reliability analysis of dam based on vine Copula function - Qi Wu; Feng Yu; Bowen Li; Henglin Xiao; Peizhen Su; Maiyong Jiang; Guan Rong (European Journal of Environmental and Civil Engineering, 2025)

Nanoengineered polymeric RNA nanoflowers for dual-pathway modulation and effective therapy for non-small cell lung cancer - Li Wang; Dongbin Guo; Yifei Shan; Luanbiao Sun; Rong Wang; Bingmei Wang; Jiyu Guan; Quan Liu; Runze Li; Changfeng Zhu; Yicheng Zhao (Chemical Engineering Journal, 2025)

Unpacking the law of spatial directionality on urban expansion morphology and carbon emissions - Chengwei Li; ChengHe Guan; Bo Zhang; Rong Ma; Xiaoyong Chen (Sustainable Cities and Society, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

3,4-seco-Prenyllabdane sesterterpenoids and 3,4-seco-labdane diterpenoids with Zika virus inhibitory potential from Callicarpa nudiflora - Xue-Wen Wu; Guan-Rong Qiao; Xue-Rong Zhao; Qi Li; Muhammad Aurang Zeb; Xiao-Li Li; Chang-Bo Zheng; Wei-Lie Xiao (Phytochemistry, 2025)

Methanogenic response of paddy soils exposed to zinc oxide nanoparticles and sulfurized products - Minghao He; Rong Tang; Fengyi Guan; Weijie Peng; Jinrong Lu; Keyi Li; Lihua Zhou; Yujie Wang; Yong Yuan (Journal of Hazardous Materials, 2025)

Rapid start-up and sustained performance of an anaerobic biofilm reactor for nitrogen removal in low C/N wastewater: Characterization and microbial community analysis of the PD/A process - Yuezhen Liang; Miao Liu; Rong Zhao; Kaiyu Hou; Xiaoqin Chen; Xiaojun Fan; Li Yu; Abuliti Abudula; Guoqing Guan; Yun Duan (Journal of Environmental Chemical Engineering, 2025)

Experimental study on mechanical behavior of basalt under different freeze–thaw conditions - Bowen Li; Ruotao Liu; Qinyan Qiu; Huqi Zhang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2025)

Machine learning for time series prediction of valley deformation induced by impoundment for high arch dams - Hang-Hang Zang; Dian-Qing Li; Xiao-Song Tang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2025)

Recent advancements in cation-intercalated vanadium oxide cathode materials for zinc-ion batteries - Kunxuan Li; Rong Li; Tiantian Guan; Lei Wang; Lingling Xie; Qing Han; Xuejing Qiu; Xiaoyu Cao; Limin Zhu (Chemical Engineering Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The influence of carbon dioxide on fermentation products, microbial community, and functional gene in food waste fermentation with uncontrol pH - Xin-Rong Pan; Pei-Ken Shang-Guan; Shu-Hui Li; Chu-Hao Zhang; Jia-Min Lou; Liang Guo; Lu Liu; Yin Lu (Environmental Research, 2025)

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Assessment of carbon emissions and reduction potential in China's copper smelting industry - Rong Gao; Yao Shi; Chun Cao; Huiquan Li; Yuanbo Xie; Jingjing Shi; Chenmu Zhang; Xue Guan (Journal of Industrial Ecology, 2024)
As the largest producer and consumer of copper, China is facing enormous challenges from carbon peaking and neutrality. This article adopts “bottom‐up” and “top‐down” methods to construct a more accurate model, to predict the CO 2 emissions of China's copper smelting industry, and explores its potential for carbon reduction in the future from three scenarios as the baseline scenario (BAU), the general low‐carbon (NLC), and the enhanced low‐carbon (ELC). The results show that the CO 2 emissions can achieve a peak in 2028 either in NLC or ELC scenarios, with a peak range of 14.9–16.88 million tonnes. Prior to reaching the peak, the contributions of energy adjustment, material substitution, and process selection to carbon reduction have significantly improved, and the contribution rates increased from 30.91%, 4.11%, and 1.46% to 42.7%, 32.07%, and 15.63% in ELC scenario. After the peak, the contribution of energy adjustment gradually slows down, while the material substitution continues to increase, and the contribution rates increased from 21.25% and 32.07% to 29.38% and 40.01% in NLC and ELC scenarios. In the future, concentrate oxygen‐enriched bottom‐blowing smelting and direct refining from waste copper anode furnaces show ideal potential for carbon reduction before 2025, increasing the proportion of recycled copper production, and adjusting energy structure will be more effective from 2025 to 2035. The conclusions of this study can provide a scientific basis for formulating policy recommendations for green and low‐carbon development of the copper industry in China and all over the world in the future.

Efficient Bayesian updating for deformation prediction of high rock slopes induced by excavation with monitoring data - Dian-Qing Li; Hang-Hang Zang; Xiao-Song Tang; Guan Rong (Engineering Geology, 2024)

Ti2TaC2: A novel out-of-plane ordered MXene towards flexible and cytocompatible supercapacitors - Yunfeng Guan; Lixian Jiang; Rong Zhao; Xuanke Li; Hui Zhu; Qin Zhang; Zhijun Dong; Nianjun Yang; Ye Cong (Chemical Engineering Journal, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Response to Discussion on “Thermal Effect Promotes Non-Darcian Flow in Heated Rock Fractures” - Jie Tan; Guan Rong; Changdong Li; Jia-Qing Zhou; Huiming Tang (Rock Mechanics and Rock Engineering, 2024)

LC-MS-based untargeted metabolomics reveals the mechanism underlying prostate damage in a type 2 diabetes mouse model - Rong Qi; Shao-san Kang; Yongchao Pei; Mingming Liu; Yufan Zhou; Bo Guan; Xinduo Zhang; Zhiguo Li; Fenghong Cao (Reproductive Biology, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Ferrous ion enhanced Fenton-like degradation of emerging contaminants by sulfidated nanosized zero-valent iron with pH insensitivity - Jia-Qi Chen; Guan-Nan Zhou; Rong-Rong Ding; Qi Li; Han-Qing Zhao; Yang Mu (Journal of Hazardous Materials, 2023)

Thermal Effect Promotes Non-Darcian Flow in Heated Rock Fractures - Jie Tan; Guan Rong; Changdong Li; Jia-Qing Zhou; Huiming Tang (Rock Mechanics and Rock Engineering, 2023)

One new elemane sesquiterpenoid glycoside and five glycoglycerolipids from Pittosporum truncatum with anti-bacterial activity - Rong Huang; Ji-Li Deng; Sheng-Nan Guan; Jia-Qi Ding; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Mode I fracturing behavior of Malan loess and implications for the toppling failure of loess slopes - Rong Wang; Yanrong Li; Fanfan Guan; Weiheng Fan; Tianyu Ma (Engineering Geology, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Identification and genetic characterisation of cathepsin L in Demodex - Hu Li; Guan Chenglin; Zhao Yae; Zhang Wanyu; Chai Rong (Experimental and Applied Acarology, 2023)

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Poly(ionic liquid) boosts overall performance of electrocatalytic reduction of low concentration of CO gas - Guo-Yi Duan; Xiao-Qiang Li; Jun-Wu Chen; Guang-Rong Ding; Peng-Xin Guan; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Genetic diversity of Lathyrus sp collected from different geographical regions - Md. Mosiur Rahman; Md. Ruhul Quddus; Md. Omar Ali; Rong Liu; Mengwei Li; Xin Yan; Guan Li; Yishan Ji; Md. Monoar Hossain; Chenyu Wang; Ashutosh Sarker; Tao Yang; et al. (Molecular Biology Reports, 2022)

Circulating microRNA-30a-5p, microRNA-101-3p, microRNA-140-3p and microRNA-141-3p as potential biomarkers for dexmedetomidine response in pediatric patients - Xinmei Cai; Bilian Li; Wei Wei; Yanping Guan; Xue Bai; Min Huang; Yaying Huang; Lili Rong; Xingrong Song; Guoping Zhong (European Journal of Clinical Pharmacology, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Development and application of the Faba_bean_130K targeted next-generation sequencing SNP genotyping platform based on transcriptome sequencing - Chenyu Wang; Rong Liu; Yujiao Liu; Wanwei Hou; Xuejun Wang; Yamei Miao; Yuhua He; Yu Ma; Guan Li; Dong Wang; Yishan Ji; Hongyan Zhang; et al. (Theoretical and Applied Genetics, 2021)

A new atypical short‐chain dehydrogenase is required for interfungal combat and conidiation in Trichoderma guizhouense - Hong Zhu; Jian Zhang; Qi Gao; Guan Pang; Tingting Sun; Rong Li; Zhenzhong Yu; Qirong Shen (Environmental Microbiology, 2021)
Summary Hypocrealean Trichoderma are the most extensively studied facultative mycoparasites against phytopathogenic fungi. Aerial hyphae of Trichoderma guizhouense can rapidly proliferate over Fusarium oxysporum hyphae, cause sporadic cell death and arrest the growth of the host. The results of the present study demonstrated that a unique short‐chain dehydrogenase/reductase (SDR), designated as TgSDR1, was expressed at a high level in T . guizhouense challenged by the hosts. Similar to other SDRs family members, the TgSDR1 protein contains a cofactor‐binding motif and a catalytic site. The subcellular localization assay revealed that the TgSDR1::GFP fusion protein translocated to lipid droplets in mycelia and conidia. The data obtained using reverse genetic approach indicated that TgSDR1 is associated with antifungal ability, plays an important role in providing reducing equivalents in the form of NADPH and regulates the amino sugar and nucleotide sugar metabolism in T . guizhouense upon encountering a host. Moreover, the TgSDR1 deletion mutant was defective in conidiation. Thus, TgSDR1 functions as a key metabolic enzyme in T . guizhouense to regulate mycotrophic interactions, defence against other fungi, such as F . oxysporum , and conidiation.

Influencing factors and physiochemical changes of embryogenesis through in vitro isolated microspore culture in Brassica species - Yan-Qi Dong; Yu-Hong Gao; Te Zhao; Guang-Qian Ren; Yan-Li Liu; Bin Guan; Rong-Xian Jin; Fei Gao; Yan-Li Zhang; Xiu-Fang Tan; Hong-Cai Zhu; Yu-Hong Zhang; et al. (Biologia, 2021)

Effect of thermal damage on mechanical and permeability properties of sandstone - Guan Rong; Bowen Li; Junsong Quan; Zhiheng Chen; Shiqian Meng; Jun Peng (Arabian Journal of Geosciences, 2021)

A temperature-induced chitosanase bacterial cell-surface display system for the efficient production of chitooligosaccharides - Qianqian Li; Tuantuan Wang; Yangzhi Ye; Shimin Guan; Baoguo Cai; Shuo Zhang; Shaofeng Rong (Biotechnology Letters, 2021)

Experimental Investigation on Physical and Mechanical Properties of Granite Subjected to Cyclic Heating and Liquid Nitrogen Cooling - Guan Rong; Song Sha; Bowen Li; Zhiheng Chen; Ziyang Zhang (Rock Mechanics and Rock Engineering, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Experimental Evaluation of Physical and Mechanical Properties of Geothermal Reservoir Rock after Different Cooling Treatments - Song Sha; Guan Rong; Zhiheng Chen; Bowen Li; Ziyang Zhang (Rock Mechanics and Rock Engineering, 2020)

An Innovative Method to Evaluate Hydraulic Conductivity of a Single Rock Fracture Based on Geometric Characteristics - Jie Tan; Guan Rong; Hongbin Zhan; Renhui He; Song Sha; Bowen Li (Rock Mechanics and Rock Engineering, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

Genetic diversity analysis for narrow-leafed lupin (Lupinus angustifolius L.) by SSR markers - Yishan Ji; Rong Liu; Jinguo Hu; Yuning Huang; Dong Wang; Guan Li; Md. Mosiur Rahman; Hongyan Zhang; Chenyu Wang; Mengwei Li; Tao Yang; Xuxiao Zong (Molecular Biology Reports, 2020)

Tensile strength and brittleness of sandstone and granite after high-temperature treatment: a review - Song Sha; Guan Rong; Jie Tan; Renhui He; Bowen Li (Arabian Journal of Geosciences, 2020)

MiR-145 alleviates Hcy-induced VSMC proliferation, migration, and phenotypic switch through repression of the PI3K/Akt/mTOR pathway - Minghao Zhang; Fan Li; Xiuyu Wang; Jian Gong; Yushan Xian; Guan Wang; Zihan Zheng; Chenxu Shang; Bo Wang; Yanhao He; Weirong Wang; Rong Lin (Histochemistry and Cell Biology, 2020)

Molecular cloning and characterization of genes related to the ethylene signal transduction pathway in pomegranate (Punica granatum L.) under different temperature treatments - Rong Huang; Wei Li; Xiao-Wan Guan; Biao Xie; Shui-Ming Zhang (Journal of Biosciences, 2019)

Effect of Open-Fire-Induced Damage on Brazilian Tensile Strength and Microstructure of Granite - Song Sha; Guan Rong; Jun Peng; Bowen Li; Zhijun Wu (Rock Mechanics and Rock Engineering, 2019)

The Effect of Surface Wettability and Wall Roughness on the Residual Saturation for the Drainage Process in Sinusoidal Channels - Long Cheng; Xiaofan Li; Guan Rong; Chuangbing Zhou (Transport in Porous Media, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

Using a new framework of two-phase generalized additive models to incorporate prey abundance in spatial distribution models of juvenile slender lizardfish in Haizhou Bay, China - Ying Xue; Kisei Tanaka; Huaming Yu; Yong Chen; Lisha Guan; Zengguang Li; Haiqing Yu; Binduo Xu; Yiping Ren; Rong Wan (Marine Biology Research, 2018)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

Chronological constraints on the tectonic evolution of the Chinese Tianshan Orogen through detrital zircons from modern and palaeo-river sands - Rong Ren; Shu-Wei Guan; Bao-Fu Han; Li Su (International Geology Review, 2017)

Trichoderma-enriched organic fertilizer can mitigate microbiome degeneration of monocropped soil to maintain better plant growth - Guan Pang; Feng Cai; Ruixia Li; Zheng Zhao; Rong Li; Xiaolong Gu; Qirong Shen; Wei Chen (Plant and Soil, 2017)

Host shoot clipping depresses the growth of weedy hemiparasitic Pedicularis kansuensis - Xiao-Lin Sui; Wei Huang; Yun-Ju Li; Kai-Yun Guan; Ai-Rong Li (Journal of Plant Research, 2015)

Bacteriological and virulence study of a Mycobacterium chimaera isolate from a patient in China - Guan Liu; Su-Ting Chen; Xia Yu; Yu-Xun Li; Ying Ling; Ling-Ling Dong; Su-Hua Zheng; Hai-Rong Huang (Antonie van Leeuwenhoek, 2015)

Arbuscular mycorrhizal fungi: potential biocontrol agents against the damaging root hemiparasite Pedicularis kansuensis? - Xiao-Lin Sui; Ai-Rong Li; Yan Chen; Kai-Yun Guan; Lu Zhuo; Yan-Yan Liu (Mycorrhiza, 2014)

Effects of High Zinc Levels on the Lipid Synthesis in Rat Hepatocytes - Xinwei Li; Yuan Guan; Xiaoxia Shi; Hongyan Ding; Yuxiang Song; Chenggang Li; Rong Liu; Guowen Liu (Biological Trace Element Research, 2013)

Cloning and characterization of a thermostable carboxylesterase from inshore hot spring thermophile Geobacillus sp. ZH1 - Yanbing Zhu; Guangming Liu; Hebin Li; Jingwen Liu; Xiaoming Bai; Rong Guan; Huinong Cai (Acta Oceanologica Sinica, 2012)

Association of PDE4B polymorphisms and schizophrenia in Northwestern Han Chinese - Fanglin Guan; Chen Zhang; Shuguang Wei; Hongbo Zhang; Xiaomin Gong; Jiali Feng; Chengge Gao; Rong Su; Huanming Yang; Shengbin Li (Human Genetics, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Genetic Polymorphisms of the CACNA2D1 Gene and Their Association with Carcass and Meat Quality Traits in Cattle - Guan-Yu Hou; Zheng-Rong Yuan; Xue Gao; Jun-Ya Li; Hui-Jiang Gao; Jin-Bao Chen; Shang-Zhong Xu (Biochemical Genetics, 2010)

Arbuscular mycorrhizal fungi may serve as another nutrient strategy for some hemiparasitic species of Pedicularis (Orobanchaceae) - Ai-Rong Li; Kai-Yun Guan (Mycorrhiza, 2008)

Mycorrhizal and dark septate endophytic fungi of Pedicularis species from northwest of Yunnan Province, China - Ai-Rong Li; Kai-Yun Guan (Mycorrhiza, 2007)